PENINGKATAN BERPIKIR KRITIS DAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK MENGGUNAKAN MODEL PBL DENGAN PENDEKATAN CRT MATERI STATISTIKA SMPN 14 MADIUN - Clarissa Okta Berliananda; Sardulo Gembong; Lilik Sulistyawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Learning activities that do not focus on the background of students and lack of problem solving make learning less meaningful and result in low critical thinking skills, especially in mathematics learning. This study aims to improve critical thinking skills and mathematics learning outcomes of students through the application of the Problem-Based Learning (PBL) model with the Culturally Responsive Teaching (CRT) approach. The subjects of the study were 27 students of class VIII C of SMP Negeri 14 Kota Madiun in the 2023/2024 academic year. This study used the Classroom Action Research (CAR) method with the Kurt Lewin model research design, which was carried out in two cycles including planning, action, observation, and reflection. The results of the study showed an increase in students' critical thinking skills, marked by an increase in five assessment indicators: Providing Simple Explanations, Building Basic Skills, Concluding, Making Further Explanations, and Developing Strategies and Tactics. The percentage of critical thinking skills increased from 66.4% in the pre-cycle, to 72.1% in cycle I, and 83.0% in cycle II. In addition, learning outcomes also increased from 28.125% in the pre-cycle, to 75% in cycle I, and 84.4% in cycle II. In conclusion, the PBL model with the CRT approach is effective in improving students' critical thinking skills and mathematics learning outcomes.